Calidad de consejería y cumplimiento de vacunas en madres de menores de 1 año del establecimiento de Salud América Iquitos 2024 - Vasquez Bardales, Andrith Aldahir (2024)
The objective was to determine the relationship between the quality of vaccine counseling and vaccine compliance according to the vaccination schedule, in mothers of children under 1 year of age, of the América health establishment, Iquitos 2024. It is a quantitative, non-experimental, descriptive, cross-sectional and correlational study; made up of 40 mothers with children under 1 year of age. Survey and observation were used as techniques; and instruments: a questionnaire on the quality of vaccination counseling (92.50% validity and 82.34% reliability) and a record of compliance with the vaccination schedule. The results obtained were: average age of mothers (27.3±6.6); cohabitants 75% (30) and single 25% (10); secondary 77.5% (31), technical/higher 20% (8) and primary 2.5% (1); housewives 85% (30), students 7.5% (3) and independent 7.5% (3); Catholics 75% (30), evangelicals 22.5% (9) and others 2.5 (1). 60.0% (24) rated the quality of the counseling in vaccine administration as good, 32.5% (13) regular and 7.5% poor (3); according to dimensions: before, 90% (36) good, 7.5% (3) fair and 2.5% bad (1); during, 62.5% (25) good, 32.5% (13) fair and 2.5% (1) bad; and then, 57.5% (23) regular, 40% (16) good and 2.5% (1) bad. Regarding compliance with the vaccination schedule, 77.5% (31) did not comply and 22.5% (9) did. Concluding that there is no significance between the quality of vaccine counseling and compliance with vaccines according to the vaccination schedule in children under 1 year of age, of the América health establishment (0.886 > 0.05).